2021
DOI: 10.3390/molecules26206129
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Study on Redox Potential Control of Iron-Sulfur Cluster by Hydrogen Bonds: A Possibility of Redox Potential Programming

Abstract: The effect of hydrogen bonds around the active site of Anabaena [2Fe-2S] ferredoxin (Fd) on a vertical ionization potential of the reduced state (IP(red)) is examined based on the density functional theory (DFT) calculations. The results indicate that a single hydrogen bond increases the relative stability of the reduced state, and shifts IP(red) to a reductive side by 0.31–0.33 eV, regardless of the attached sulfur atoms. In addition, the IP(red) value can be changed by the number of hydrogen bonds around the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Note that it is generally difficult to discuss the contribution only to hydrogen bonding because the electrostatic potential of the surrounding amino acids also affects the S atomic charges. However, previous work has considered that the hydrogen bonding affects the S atomic charges in Fe–S clusters. , Thus, the hydrogen bonding of the [4Fe–4S] cluster with sulfur is expected to control the interactions taking place within the cluster. Previous DFT calculations of the model [4Fe–4S] complexes showed that the difference of 0.1–0.2 Å in the Fe–S distance and the existence or nonexistence of hydrogen bonds affect their spin states .…”
Section: Resultsmentioning
confidence: 99%
“…Note that it is generally difficult to discuss the contribution only to hydrogen bonding because the electrostatic potential of the surrounding amino acids also affects the S atomic charges. However, previous work has considered that the hydrogen bonding affects the S atomic charges in Fe–S clusters. , Thus, the hydrogen bonding of the [4Fe–4S] cluster with sulfur is expected to control the interactions taking place within the cluster. Previous DFT calculations of the model [4Fe–4S] complexes showed that the difference of 0.1–0.2 Å in the Fe–S distance and the existence or nonexistence of hydrogen bonds affect their spin states .…”
Section: Resultsmentioning
confidence: 99%
“…With the possibility of spin delocalization ruled out, broken symmetry (BS) DFT calculations on the low-spin as well as a high-spin (triplet) calculation were performed using a ∼300 atom model (Figure S7) of the Ni p (II)–Me species, A Me ( 4′ ) (Figure e–g and Tables S5–S7) to better understand the potential electronic configurations and structures in question. DFT and TD-DFT have been successfully employed in prior investigations to describe the electronic and geometric structures of ACS and other biological Fe–S clusters. , Both BS-low-spin and high-spin ground states converged to approximately square planar geometries. The low-spin configuration was lower in energy (∼8.8 kcal mol –1 ) and showed better agreement with the experimental data.…”
Section: Resultsmentioning
confidence: 99%
“…A. aromaticum EbN1 T has a small number of enzymes using FAD as a cosubstrate. Instead, it uses ferredoxin (13 enzymes) with its wide range of redox potentials ( 55 ), particularly in the degradation pathways of aromatic compounds. Moreover, A. aromaticum EbN1 T possesses several enzymes that transfer electrons between NAD, NADP, ferredoxin, flavodoxin, ETFs, and ubiquinol, which enable a wide flexibility of metabolic pathways.…”
Section: Resultsmentioning
confidence: 99%